2003
DOI: 10.1111/1540-4781.00204
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Flow Theory in the Foreign Language Classroom

Abstract: This article focuses on the relationship between flow experiences and language learning. Flow Theory suggests that flow experiences (characterized by a balance between challenge and skills and by a person's interest, control, and focused attention during a task) can lead to optimal learning. This theory has not yet been tested in the area of foreign or second language learning. The purpose of the present study is twofold: first, to establish the foundation for a research stream addressing flow in language lear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
237
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 210 publications
(260 citation statements)
references
References 31 publications
21
237
0
2
Order By: Relevance
“…The concept of flow is considered particularly relevant to the investigation of learning processes, and several scholars have investigated the specific factors fostering optimal experience in education [16,[20][21][22][23][24][25]. While Csikszentmihalyi investigated flow mainly at the individual level, Sawyer [11,15] extended this concept to the study of group collaboration, with the purpose of understanding which features facilitate optimal group experience and its relationship with creative performance.…”
Section: Key Concepts and Termsmentioning
confidence: 99%
“…The concept of flow is considered particularly relevant to the investigation of learning processes, and several scholars have investigated the specific factors fostering optimal experience in education [16,[20][21][22][23][24][25]. While Csikszentmihalyi investigated flow mainly at the individual level, Sawyer [11,15] extended this concept to the study of group collaboration, with the purpose of understanding which features facilitate optimal group experience and its relationship with creative performance.…”
Section: Key Concepts and Termsmentioning
confidence: 99%
“…According to Egbert (2003) the participants who averaged 5.0 or above on any survey (equivalent to agree on all questions) are believed to have experienced flow. In this respect, previous research designates the flow experience as being above average on skill and challenge.…”
Section: Resultsmentioning
confidence: 99%
“…A few studies which have applied flow theory in language learning have confirmed the relationship between flow and classroom language learning (Egbert, 2003;Ghonsooly & Hamedi, 2014;McQuillan & Conde, 1996;Schmidt & Savage, 1992). As noted, among the classroom activities, reading is reported as a flow inducing task in that the recreation of the writer's intended meaning can be accomplished only when the reader integrates the textual information with his background knowledge (Haji Maibodi, 2008).…”
Section: Flow In Language Learning and Readingmentioning
confidence: 97%
See 2 more Smart Citations